INNOVATIVE APPROACHES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Xolmo‘minova Mavluda Rustam qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Innovative approaches in teaching English as a foreign language have transformed the traditional classroom into a dynamic and interactive learning environment. This article explores modern methods, including gamification, flipped classroom, blended learning, and the use of artificial intelligence tools. The practical applications of these approaches are analyzed, highlighting their impact on students’ motivation, engagement, and language acquisition. By integrating innovative strategies, teachers can enhance students’ communicative competence and critical thinking skills while fostering a more enjoyable and effective learning experience.